Nonlinear Control Technology of Vehicle Chassis-by-Wire System - Zhao, Wanzhong; Wang, Chunyan (Recent Advancements in Connected Autonomous Vehicle Technologies, 2022)
IX, 241 p. 162 illus., 126 illus. in color.